An evaluation of the safety and preliminary efficacy of peri‐ and post‐operative treprostinil in preventing ischemia and reperfusion injury in adult orthotopic liver transplant recipients. Issue 6 (5th May 2021) - Almazroo, Omar Abdulhameed; Miah, Mohammad Kowser; Pillai, Venkateswaran C.; Shaik, Imam H.; Xu, Ruichao; Dharmayan, Stalin; Johnson, Heather J.; Ganesh, Swaytha; Planinsic, Raymond M.; Demetris, Anthony J; Al‐Khafaji, Ali; Lopez, Roberto; et al.
Abstract: Background: Orthotopic liver transplantation (OLT) is the only treatment option for various end‐stage liver diseases. Ischemia and reperfusion (I/R) injury is one of the unavoidable complications/conditions in OLT. In 2019, a total of 8896 livers were transplanted of which >94% organs were procured from deceased donors. An increase in the use of extended criteria donor (ECD) livers for transplantation further unraveled the role of hepatic I/R injury on short‐term and long‐term graft outcomes. Despite promising outcomes with the use of antioxidants, free radical scavengers, and vasodilators; I/R‐mediated liver injury persists and significantly influences the overall clinical outcomes. Treprostinil, a synthetic prostacyclin I2 (PGI2 ) analog, due to its vasodilatory property, antiplatelet activity, and its ability to downregulate pro‐inflammatory cytokines can potentially minimize I/R injury. Aim: We investigated the safety and preliminary efficacy of continuous intravenous infusion of treprostinil in liver transplant recipients in a prospective, single‐center, non‐randomized, interventional study. Material and methods: This was a dose escalation (3 + 3 design) phase 1/2 study. Deceased donor liver transplant recipients received 5 ng/kg/min for two days, or 2.5, 5, and 7.5 ng/min/kg for 5 days as a continuous infusion. Multiple blood samples were collected for biochemical parameter assessment and for measuring treprostinil levels. Indocyanine green plasma disappearance rate was used as a measure of hepatic functional capacity. Results: Subjects tolerated continuous infusion of treprostinil up to 5 ng/kg/min for 120 h with no occurrence of primary graft non‐function (PNF), minimized need for ventilation support, reduced hospitalization time, 100% graft and patient survival, and improved hepatobiliary excretory function comparable to normal healthy adults. Discussion: Treprostinil can be administered to liver transplant patients safely during the perioperative period. Conclusion: Based on this phase 1/2 study, further efficacy studies of treprostinil in preventing I/R injury of liver should be conducted to potentially increase the number of livers available for transplantation.